INFRASTRUCTURE DEVELOPMENT: POLITENESS STRATEGY IN THE SPEECH OF THE INDONESIAN PRESIDENT, JOKOWI. - Eliyana, Ema (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
Pragmatism is an important factor to take into consideration when developing political speech because the main goal of political speech is to communicate with the public and foster trust. 1) Identify the constructive and destructive forms of politeness employed in President Jokowi's statements. 2) To determine how frequently President Jokowi used positive and negative strategies in his speech. In this study, a qualitative research design was used. Using document analysis, it is possible to pinpoint the diplomatic techniques Jokowi employed during his speeches. According to the analysis, more positive politeness strategies (96,9%) than negative politeness strategies (3,1%) are used. The analysis showed that the most popular positive politeness tactics were to show greater interest in the recipient and to use in-group identity markers. The speaker only employed one impolite tactic, which was to show deference. To gain the trust of Indonesians, Jokowi primarily employs positive politeness techniques.